Evaluation the Efficacy of Combined Therapy Ketoconazole and Tamsulosinvs Tamsulosin in AUR Followed BPH Iraqi Patients - Ali Abdulbaqi Ali Ismael (Journal of Global Pharma Technology, 2018)
The Benin prostate hyperplasia symptom may began with 40years and the incidence increased with increased age to reach 30% in men aged above70 years , this associated with sever complication like AUR which associated with higher morbidity and mortality about 1:7 of patients suffering from AUR dies during the first year, So the study aimed to evaluated the efficacy of mixed therapy versus mono therapy as well as prolong period ( 5 and 8- days ) in success TWOC . This study included 100 AUR as complicated to BPA patients which divided into two groups the 1st one 50 patients treated with mixed therapy Ketoconazole and Tamsulosin for 5 Daye (25patients) and 8daye (25 patients) , While the 2nd groups treated with immunotherapy Tamsulosin for 5 day and 8 day to 25 patient for each one , then evaluate peak flow rate , Residual urine , voided volume and prostate size to determined efficient type of therapy that gave successful treatment . Results clarified that mixed therapy recorded the best results than mono-therapy and duration for 8 day revealed high PFR, voided volume and low residual urine and prostate size. In conclusion Combination therapy ( Tamsulosin and ketoconazole )augment the prospers rate of treatment without catheter in AUR person this confirmed through that patient void more successfully after catheter removal , according to duration the 8 day revealed high peak flow rate , voided volume and decreased the residual urine also , combination therapy with 8doses recommended to treatment AUR complicated BPH patients Keywords: BPA, AUR, Ketoconazole, Tamsulosin, TWOC, Combined therapy.